Identifying language learning gaps of ESL students at intermediate level in Pakistani colleges - Muhammad Arfan Lodhi (Universitat Autònoma de Barcelona, 2019)
The study attempted to evaluate the existing language proficiency level of 12th grade students and compared the results with the relevant learning standards fixed by the CEFR for these intermediate level language users. The data was collected and analyzed quantitatively from a random sample of 200 students from government and private colleges in Pakistan. A language proficiency test, checklist and questionnaire were administered as data collection instruments. The findings of the study reflected huge learning gaps between the acquired and desired proficiency levels of language learners. Data shows that the majority of the students were found at initial level of basic users for all seven language learning skills i.e. reading, writing, listening, speaking, vocabulary, grammar and sociolinguistic appropriateness. It is highly recommended to adopt appropriate and effective instructional plans to increase the language proficiency level of students up to the required standards.